Special issue on public sector enhancement in Pacific Island states - Hassall, Graham (2018)
This editorial introduction sets the scene for the analyses in the following research articles. It identifies several significant challenges facing the public sectors of Pacific Island states. The challenges are universal, while being especially pressing in Island countries with limited resource bases and circumstances mostly of geographical smallness and spread which affect administrative capacities for fostering essential socio-economic development. The states whose public sector arrangements are addressed in the articles are the Cook Islands, Papua New Guinea, Vanuatu, the Solomon Islands, and Samoa. - Reproduced.